ANALISIS TREND KINERJA KEUANGAN BANK KALTIM - Andi Indrawati (RJABM (Research Journal of Accounting and Business Management), 2017)
The object of this study is Bank Kaltim financial statements that have been audited by independent auditors. Research data obtained through documentation. This research includes descriptive research. In order to analyze the development of financial performance from 2017-2019, researcher used trend analysis technique.Trend analysis is a method of statistical analysis that is intended to make an estimate or forecast the future. To do a good forecasting is needed various kinds of information (data) is quite a lot and observed in a period of relatively long, so that the analysis can determine how many big fluctuations and the factors that influence those change. The profitability ratios will provide an overview of the effectiveness of the management of the company. The greater the profitability means the better, because the prosperity of the owner of the company increased with greater profitability. Profitability ratios consist of Profit Margin, Basic Earning Power, Return on Assets and Return on Equity.